PENGARUH STRUKTUR CORPORATE GOVERNANCE DAN FINANCIAL INDICATORS TERHADAP KONDISI FINANCIAL DISTRESS - Oktita Earning Hanifah; Agus Purwanto (Diponegoro Journal of Accounting, 2013)
This study investigates the impact of corporate governance structure and financial indicators on financial distress. The corporate governance structure in this study using the indicator size of the board of directors, the board size, independent commissioners, managerial ownership, institutional ownership, and the size of the audit committee. While financial indicators use liquidity, leverage, profitability, and operating capacity. The population in this study are all of the manufacturing companies listed on the Indonesia Stock Exchange and is continously published financial statements in the year 2009-2011. Based on purposive sampling method, samples obtained is 45 companies in the period 2009-2011 so obtain 135 observations. The criteria of financial distress in this study was measured by using interest coverage ratio. This study used logistic regression as a data analysis tool. The result of this research showed that director size, manajerial ownership, institutional ownership, leverage and operating capacity have significant impact on the financial distress condition. This research failed to prove effect of commissioners size, independent commissioners, size of the audit committee, liquidity and profitability with probability of experiencing financial distress.